BARITO RIVERSIDE PUBLIC OPEN SPACE IN MUARA TEWEH CITY - Farhani, Muhammad Reza; Heldiansyah, J. C. (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
The Regional Government of North Barito Regency carried out an image of Muara Teweh City with the titles "wonderful Barito" and "Muara Teweh Barito City" which resulted in the existence of a siring construction plan along the banks of the Barito river Muara Teweh City. The siring development plan along the Barito river, besides acting as a public open space, also acts as an effort to beautify the city's visuals, it is better to consider the lives of the local community. The design of the Barito riverside public open space with the cultural riverside concept can be an answer to the need for riverside public open space that not only accommodates recreational activities for visitors by utilizing the Barito river landscape, but can also accommodate the cultural activities of the local community without getting rid of the community's riverside life.